Pointilisme digital - pengkaryaan dimensi baru - Soon, C.L (Universiti Malaysia Sarawak, UNIMAS, 2006)
Digital Pointilism- The New Dimension. An artwork that requires interpretation and imagination of the audience in order to appreciate the artwork. However, the variation of perception and views sometimes confused the views in identifying the displayed visual. With the supporting audio and the motion effects in the visual, the audience will be able to visualize the message that the artist trying to convey.